(untitled) (International Journal of Nursing Education, 2021)
Gaps in generation and timely transfer of relevant information during care transitions remain a great challenge to care coordination. Electronic Health Record (EHR) based information transfer tools are not efficiently used by most providers. The objective of this project was to understand the current process of care transition between ambulatory and inpatient care setting and to explore the utilization and scope of an EHR based Longitudinal Plan of Care in improving coordination during care transition. The Longitudinal Plan of Care when compared with transition of care practices recommended by Transitions of Care Consensus Conference and National Transitions of Care Coalition work group showed that it lacked some information pertinent to care coordination. The survey performed indicated that most commonly used Electronic Health Record tool for care transition were notes and chart reviews (97.4%, 93.4%). Only 12% of the participants expressed high satisfaction with the currently used tool. Among the participants who used the Longitudinal Plan of Care, only 8.8% reported it as a sufficient tool for information transfer. Majority (93.5%) were unaware that such a tool existed and had never explored its functionality. Improving the functionality of Longitudinal Plan of Care and training health care providers can greatly facilitate information transfer during care transition.